Suicide as a Slovenian metaphor - Zajc, Marko (Prispevki za novejšo zgodovino, 2024)
Between the 1960s and 1980s, suicide was frequently discussed as a major social issue in the Slovenian public sphere, leading to the establishment of the idea of Slovenians as a "suicide nation." In her book "Illness as Metaphor," Susan Sontag examines how society uses illness as a metaphor for moral, psychological, and political conditions, often resulting in the stigmatization of patients. This perspective is valuable for understanding the representations of suicide in socialist Slovenia. This paper analyses the influence of the metaphor of the "nation of suicides" on political thought and discourse in socialist Slovenia. It explores how intellectuals used or rejected this idea in their debates and how they adapted expert discussions and statistics to their political agendas. The concept of suicide as a "Slovenian problem" emerged in the late 1960s, supported by statistics and high-profile cases of suicide among young people from prominent cultural and political families.
Keywords: metafora; metaphor; political thought; politična misel; samomori; suicide; zgodovina